Analisis Kesiapan (Readiness Assessment) Penerapan Electronic Medical Record Di Klinik Rawat Inap PKU Muhammadiyah Pakem - Rahmat Hidayat, Anas; Permata Indonesia Yogyakarta, Ersihana Wulan Sari - (IJMS - Indonesian Journal on Medical Science, 2017)
Abstact: The medical record at the clinic in patient of pku muhammadiyah pakem is still uses manual system (paper based), the use of paper based the frequent duplicate number of patients in the medical record and occuring set of problems medicines of pharmaceutical on installation. From the live interview with the director clinic in patient of PKU Muhammadiyah Pakem of note that clinic in patient pku muhammadiyah pakem will implement the electronic medical record 2016 th. Therefore the analysis is needed to the implementation of the electronic medical record system. Analyze readiness (readiness assessment) the electronic medical record at the clinic in patient of PKU Muhammadiyah Pakem. The kind of research was descriptive research with a qualitative approach. The results showed that the Readiness infrastructure IT have not been in accordance with the theory because there were no readiness technical they are hardware and software ability. Readiness organization have not been in accordabce because there were no collaboration between management executive. Readiness resources men is according to the needs labor. Readiness already have the ideal in accordance with the needs in patient clinic PKU Muhammadiyah Pakem. Conclusion: The raediness of the implementation of Electronic Medical Record at the clinic inpatient PKU Muhammadiyah Pakem not ready.Keyword : Analysis, the implementation, electronic medical record.Â Abstrak: Pelaksanaan rekam medis di Klinik Rawat Inap PKU Muhammadiyah Pakem masih menggunakan sistem manual (paper based), permasalahan penggunaan paper based yaitu sering terjadi duplikasi nomor pasien di instalasi rekam medis dan terjadi kegesehan stok obat pada instalasi farmasi. Dari hasil wawancara langsung dengan Direktur Klinik Rawat Inap PKU Muhamadiyah Pakem diketahui bahwa Klinik Rawat Inap PKU Muhammadiyah Pakem akan menerapkan electronic medical recordÂ  pada tahun 2016. Oleh karena itu analisis kesiapan sangat dibutuhkan untuk implementasi sistem electronic medical record.Tujuan Penelitian ini adalah menganalisis kesiapan (readiness assessment) penerapan electronic medical record di Klinik Rawat Inap PKU Muhammadiyah Pakem.Jenis penelirtian yang digunakan yaitu penelitian deskriptif dengan pendekatan kualitatif.Hasil penelitian menunjukkan Kesiapan infrastruktur TI belum sesuai dengan teori karena belum ada kesiapan teknis yakni kemampuan perangkat keras (hardware) dan perangkat lunak (Software). Kesiapan organisasi belum sesuai karena belum ada kolaborasi antara manajemen eksekutif. Kesiapan sumber daya manusia sudah sesuai dengan teori karena sudah ada rencana proyeksi terhadap kebutuhan tenaga kerja. Kesiapan anggaran sudah ideal sesuai dengan kebutuhan di Klinik Rawat Inap PKU Muhammadiyah Pakem. Kesimpulan: Kesiapan penerapan Electronic Medical Record di Klinik Rawat Inap PKU Muhammadiyah Pakem belum siap. Kata Kunci : Analisis, Implementasi, Electronic Medical Record.